Seroprevalence of vaccine-preventable diseases among children and adolescents in Singapore: Results from the National Paediatric Seroprevalence Survey 2018. (March 2020) - Ng, Yixiang; Chua, Lily Ai Vee; Cui, Lin; Ang, Li Wei; Tee, Nancy Wen Sim; Lin, Raymond Tzer Pin; Ma, Stefan; Lee, Vernon Jian Ming
Highlights: A seroprevalence survey was conducted among Singapore's children and adolescents. Seroprevalence of measles and rubella antibodies were 98.2% and 94.8% respectively. Seroprevalence for diphtheria and tetanus were 97.1% and 89.3% respectively. Seroprevalence for varicella and anti-HBs were 52.9% and 45.7% respectively. Concordance between vaccination status and seroprevalence was generally observed. Abstract: Objectives: The Ministry of Health (MOH), Singapore, conducted the National Paediatric Seroprevalence Survey 2018 (NPSS 2018) to estimate the latest immunity levels against measles, rubella, varicella, diphtheria, tetanus and hepatitis B, and the seroprevalence of chronic hepatitis B virus (HBV) carriage in children and adolescents in Singapore. Methods: The survey involved prospective collection of residual sera from 1, 200 children and adolescents aged 1–17 years in two public acute hospitals. Enzyme-linked immunosorbent assays (EIA) or plague reduction neutralisation tests (PRNT) were used to determine the seroprevalence of the vaccine-preventable diseases. Results: Overall prevalence of measles and rubella antibodies among Singaporean children and adolescents aged 1–17 years were 98.2% (95% CI: 91.2–98.8%) and 94.8% (95% CI: 93.4–95.9%) respectively. 97.1% (95% CI: 96.0–97.9%) of subjects had at least basic protection against diphtheria, while 89.3% (95% CI: 87.5–91.0%) were protected against tetanus. The prevalence of chronic HBV carriage was 0.4% (95% CI: 0.2–1.0%), while 45.7% (95% CI: 42.9–48.5%) were immune against HBV. The seroprevalence for varicella antibodies was 52.9% (95% CI: 50.1–55.7%). Concordance between vaccination status and seroprevalence was observed for measles, rubella, diphtheria and tetanus. Conclusion: Singapore's children and adolescents are well-protected against measles, rubella, diphtheria and tetanus. Continual efforts in ensuring high vaccination coverage should be sustained.